Catalogue of breaches of the 1966 Geneva Agreement by Venezuela 1966-2015 ([Ministry of Foreign Affairs] GeorgetownGY, 2015)
Provides a listing of breaches, including explanations of the 1966 Geneva Agreement, by Venezuela.
Keywords: BOUNDARIES